Peran Kepuasan Pelanggan Dalam Mediasi Pengaruh Kualitas Pelayanan Dan Discount Terhadap Impulse Buying Pelanggan Toko Sepatu Stars - Purba, Rido; Sinaga, M. Arian L.; Sarwoto, Sarwoto; Cen, Cia Cai (Management And Business Progress, 2024)
This research uses approach study quantitative with type study purposeful explanatory research For analyze How connection between One variable with variable other . Population in this research is customer Stars Tebing Tinggi Shoe shop , numbering 96 people. Tools analysis : validity test, test reliability, statistical t test and indirect effect test with use Smart tools PLS 3.0.Results of this research shows that quality service influential significant to satisfaction customers , discounts   influential to satisfaction customers, quality service influential against impulse buying , discounts   influential to impulse buying , satisfaction settlement  influential to impulse buying , and  quality service as well as influence discount to satisfaction customer as intervening variable.